PEMBANGUNAN WILAYAH PERBATASAN NEGARA: GAMBARAN TENTANG STRATEGI PENGELOLAAN KAWASAN PERBATASAN DARAT DI PROVINSI KALIMANTAN UTARA - Sudiar, Sonny (Magister Administrasi Publik FISIP Universitas Mulawarman, 2015)
Development of border area always becomes an interesting discussions, this is proved when development of border area issue becomes as a part of the national development plan. For Indonesia, border area has a strategic means, especially in defence-security side, economic-trade side, and social-cultural side. This article is an effort to describe the management of land border area in North Kalimantan. They were located in both Malinau and Nunukan district spreading in 17 sub-districts which are bordered with neighboring country Malaysia. The proximity distance enabled the interactions and transborder activities among the people in land border area. Border areas in North Kalimantan have a big potential to be developed as the central of growth area, so properly policy and management are required.